Illness perceptions of gout patients and the use of allopurinol in primary care: baseline findings from a prospective cohort study. Issue 1 (December 2016) - Walsh, Ciaran; Prior, James; Chandratre, Priyanka; Belcher, John; Mallen, Christian; Roddy, Edward
Abstract Background Patients' perceptions of their illness are dynamic and can directly influence aspects of management. Our aim was to examine the illness perceptions of gout patients in UK primary care and associations with allopurinol use. Methods A health questionnaire was sent to 1805 people with gout aged ≥18 years identified by a gout diagnosis or prescriptions for allopurinol or colchicine in their primary care medical records in the preceding 2 years. The questionnaire included selected items from the revised illness perception questionnaire (IPQ-R). Associations between illness perceptions and use of allopurinol were calculated using multinomial logistic regression adjusted for age, gender, deprivation status, body mass index, alcohol consumption, comorbidities and gout characteristics. Results One thousand one hundred eighty-four participants responded to the baseline questionnaire (65.6 %). Approximately half of responders perceived that they were able to control (51.2 %) or affect their gout through their own actions (44.8 %). Three quarters perceived treatments to be effective (76.4 %) and agreed that gout is a serious condition (76.4 %). Patients who agreed that they could control their gout (Relative Risk Ratio, 95 % confidence interval 1.66 (1.12 to 2.45)) and that treatments were effective (2.24 (1.32 to 3.81)) were more likely to currently be using allopurinol than not using allopurinol. However, this significance was attenuated after adjustment for self-reported gout characteristics (1.39 (0.89 to 2.17) & 1.78 (0.96 to 3.29) respectively). Conclusions Patients who perceive that they can control their gout and that treatments are effective are more likely to be using allopurinol, this suggests that better information is needed for the patient from GPs and rheumatologist to reassure and support their use of ULT.